2014
DOI: 10.1152/ajpheart.00036.2014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aging on carotid baroreflex control of blood pressure and leg vascular conductance in women

Abstract: Recent work suggests that β-adrenergic vasodilation offsets α-adrenergic vasoconstriction in young women, but this effect is lost after menopause. Given these age-related vascular changes, we tested the hypothesis that older women would exhibit a greater change in vascular conductance following baroreflex perturbation compared with young women. In 10 young (21 ± 1 yr) and 10 older (62 ± 2 yr) women, mean arterial pressure (MAP; Finometer), heart rate (HR), cardiac output (CO; Modelflow), total vascular conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
0
31
1
Order By: Relevance
“…For this study, we focused on the baroreceptors located in the carotid sinus due to their accessibility for noninvasive manipulation. The responsiveness of the carotid baroreflex in the short-term regulation of heart rate and blood pressure can be examined quantitatively by utilizing a variable pressure neck chamber system to selectively load (simulated hypertension via neck suction) and unload (simulated hypotension via neck pressure) the carotid baroreceptors (Credeur et al 2014;Fadel et al 2003;Ludbrook et al 1977). In all familiarization and actual experimental trials, subjects were positioned semirecumbent (ϳ45°) on a patient table.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For this study, we focused on the baroreceptors located in the carotid sinus due to their accessibility for noninvasive manipulation. The responsiveness of the carotid baroreflex in the short-term regulation of heart rate and blood pressure can be examined quantitatively by utilizing a variable pressure neck chamber system to selectively load (simulated hypertension via neck suction) and unload (simulated hypotension via neck pressure) the carotid baroreceptors (Credeur et al 2014;Fadel et al 2003;Ludbrook et al 1977). In all familiarization and actual experimental trials, subjects were positioned semirecumbent (ϳ45°) on a patient table.…”
Section: Methodsmentioning
confidence: 99%
“…Five-second pulses of Ϫ60 Torr neck suction (NS) and ϩ40 Torr neck pressure (NP) were applied to load and unload the carotid baroreceptors, respectively (Credeur et al 2014;Fadel et al 2003; 2010; Kim et al 2011;Ogoh et al 2002). The neck collar (Physiology Research Instruments, Austin, TX) was fitted around the anterior two-thirds of the neck with each NS and NP stimulus being delivered 50 ms after the second consecutive R-R interval that did not vary by Ͼ50 ms using customized computer-controlled software as previously described (Credeur et al 2014;Fisher et al 2007;Potts and Raven 1995). A variable pressure source using a 3-stage vacuum/blower motor (Ametek Lamb, Berwyn, PA) in combination with a computer controlled throttle valve was used to generate the changes in neck collar pressure.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in line with our previous findings (24). Credeur et al (4) have recently observed no difference in femoral artery blood flow between young and postmenopausal women; however, Moreau et al (44) have previously found that femoral artery blood flow is impaired in postmenopausal women compared with young women: a finding that remained when normalizing to leg fat-free mass. Interestingly, they also investigated a group of postmenopausal women taking hormone replacement therapy (HRT).…”
Section: Discussionmentioning
confidence: 98%